Dimensionamento do conjunto manga de eixo, ponta de eixo e cubo de roda de um veículo Baja - Costa, Cleber Roberto (Universidade Federal de São Carlos, 2022)
The suspension of a Baja SAE vehicle is highly demanded in competitions, due to the terrain characteristics, and can show constant failures, if badly designed. Besides, the dynamics of the car are directly linked with its own mass. Therefore, a precise dimensioning of the components will represent, not just a raise in reliability, but also in performance. With the dissemination of finite element analysis software, the dimensioning of parts with complex geometries, such as the knuckle gets much easier. However, the usage of these software by users that do not have the proper knowledge to perform a structural finite element analysis is becoming very common. It is a recurrent problem in the SAE competitions recently, also affecting the Baja UFSCar team. This work intends to design a group of components that compose part of the front suspension system of a Baja SAE vehicle, the knuckle, the hub, and the stub axle. The basis of the project will be a load history provided by a simulation made in a Python algorithm. After a revision of all the theory regarding the phenomenons involved, the dimensioning of the parts have been made with the help of a CAE software, which led to a mass reduction between 19% and 30%, of the worked components, considering a finite life of 60 hours, which is enough for four competitions, considering tests, or the life cycle of the vehicle.
Sizing of steering knuckle, stub axle and wheel hub of a Baja vehicle
Keywords: Veículo Baja SAE; Dimensionamento; Análise de elementos finitos; ENGENHARIAS::ENGENHARIA MECANICA